This is my church: Seeing the internet and club culture as spiritual space - Heidi Campbell (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as Sacred Space.
Keywords: Christianity; Church; club culture; internet